2022
DOI: 10.1021/acssuschemeng.2c01578
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Cryoprotectants Enabled by Binary Natural Deep Eutectic Solvents for Sustainable and Green Cryopreservation

Abstract: Cryopreservation plays an important role in prolonging the cell viability, but non-negligible cytotoxicity of cryoprotectants restrains its further development in many areas with safety concerns such as the food industry. Inspired by cold-tolerant animals, three binary natural deep eutectic solvents (NADESs) were prepared and used as cryoprotectants for achieving cytotoxicity-free and green cryopreservation, whose cryoprotective efficiency was compared with those of glycerol and dimethyl sulfoxide (DMSO), usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…24,25 DESs are prepared by mixing a hydrogen bond donor (HBD), such as an alcohol, carboxylic acid, amide, and amino acid, and a hydrogen bond acceptor (HBA), such as cholinium chloride ([Ch]Cl), which interacts via hydrogen bonding and sometimes via electrostatic and van der Waals interactions. [26][27][28] Other than having a low melting point and convenient preparation, DESs have gained superiority due to their high atom economy, biodegradability, and their ability to be easily re-used and recycled. 29 Among many different HBAs, [Ch]Cl is the most commonly used HBA because of its biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 DESs are prepared by mixing a hydrogen bond donor (HBD), such as an alcohol, carboxylic acid, amide, and amino acid, and a hydrogen bond acceptor (HBA), such as cholinium chloride ([Ch]Cl), which interacts via hydrogen bonding and sometimes via electrostatic and van der Waals interactions. [26][27][28] Other than having a low melting point and convenient preparation, DESs have gained superiority due to their high atom economy, biodegradability, and their ability to be easily re-used and recycled. 29 Among many different HBAs, [Ch]Cl is the most commonly used HBA because of its biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from serving as a cryopreservation agent, DMSO can also markedly improve the mechanical properties of the resulting hydrogel, 44 due to the hydrogen bonds between DMSO and H 2 O dispersing pressure in the matrix. 45 Besides, it was reported that strong intermolecular hydrogen bonds among DMSO and H 2 O will give rise to PVA crystallization due to a lack of solvation of PVA chains. 38 Thus, DMSO is also beneficial to the gelation of PVA.…”
Section: Resultsmentioning
confidence: 99%
“…However, the freeze–thaw conditions for this process are less than ideal, resulting in a low supply of RBCs. In cryopreservation, mechanical damage caused by ice formation and growth severely destroys the plasma membrane, leading to RBC death [ 46 ]. The interaction of water molecules is precisely correlated with ice formation and growth.…”
Section: Discussionmentioning
confidence: 99%